Age and growth in different stocks of striped snakehead Channa striata (Bloch, 1793) inhabiting the three rivers of Gangetic river system - Khan, Salman; Khan, M. Afzal; Khan, Shahista (Indian Journal of Fisheries, 2022)
Age was estimated using different types of otoliths (sagittae, lapilli and asterisci) collected from 486 specimens of Channa striata (Bloch, 1793) from three Indian rivers, the Ganga, Gomti and Yamuna, during the period November 2012 - August 2015. The size range of the specimens was 15-70 cm total length (TL). The age estimates were compared and assessed for potential bias between readers and between pairs of aging structures. Due to the highest percentage of agreement and lowest average percentage of error and coefficient of variation values between readers, sagittae were found to be the most suitable aging structure for C. striata. When sagittae age reading were compared with those from lapilli and asterisci, the percentage of agreement was found to be highest between estimates of sagittae and lapilli. Mean values of age estimate from sagittae were comparable (p>0.05) to the values obtained from lapilli but significantly (p<0.05) different with that of asterisci. Thus, sagittae emerged as the preferred otolith for age estimation in C. striata followed by lapilli. The growth of C. striata was assessed by examining annual growth increments on sectioned sagittae. The parameters of von Bertalanffy growth equations for the fish in the selected rivers were: Lt = 94.4 (1-e-0.15(t+1.07)) for river Ganga, Lt = 93.7 (1-e-0.15(t+0.96)) for river Yamuna and Lt = 96.9 (1-e-0.14(t+1.02)) for river Gomti. The growth performance index was highest in fish stocks collected from river Ganga (3.13) followed by river Gomti (2.96) and river Yamuna (2.38). Marginal increment analysis suggested annual periodicity of the growth band formation. Keywords: Ageing precision, Channa striata, Marginal increment analysis, Otoliths, VBGF